Spiral Representation Of Spatial Feature for Spatial Color Based Image Retrieval - Narayanan, A/L N. Kulathu Ramaiyer; Wang, Hui Hui; Wang, Yin Chai; Abdelhamid, Abdesselam (2003)
In this paper, we present a new approach for retrieving similar images based on color-spatial feature. We propose the Spiral Representation Spatial Feature for images, which is rotation and scaling invariant. The Spiral Representation Spatial Feature is based on bit signature approach. The feature is extracted based on the Spiral Extraction Method, where the sub area is extracted in a circular manner, starting from the inner square and read in counter clockwise direction. The starting point of every square is the left upper sub area. The derivation of the rotated spatial features is proposed to be used for retrieval of rotated images. As an additional to common matching of whole images, partial image matching has been introduced to compliment the whole image matching, where the same images with different sizes and scaled, are retrieved as similar images, and also to locate the similar image appeared as sub image in another whole image.